STRATEGI PENGEMBANGAN PELAKSANAAN PENERIMAAN MAHASISWA BARU SEKOLAH TINGGI AGAMA ISLAM MA’HAD ALY AL-HIKAM MALANG - Alfin Nur Zakiyah (STAI Ma'had Aly Al-Hikam Malang, 2022)
Admission of new students is an important element in an educational institution, especially universities. Higher education institutions must carry out a development in order to remain competitive with other institutions. An Islamic boarding school based in Malang, namely STAI Ma'had Aly Al-Hikam Malang. This private institution is able to compete with other institutions by carrying out developments on new student admissions..The purpose of this study was to analyze the strategy for developing the implementation of new student admissions at STAI Ma'had Aly Al-Hikam Malang. The analytical method used is swot analysis, namely strengths, weaknesses, opportunities and threats. Comparing the swot elements in the implementation of new student admissions with the average number of registrants in each period.The results of this study are first, the implementation of new student admissions at STAI Ma'had Aly Al-Hikam Malang who has gone through the stages of new student admissions which include; committee formation, candidate requirements, registration, selection test, announcement of selection results and student orientation. Second, the analysis of the new student admissions development strategy carried out by the swot analysis method, it can be seen that this institution has made developments that are adapted to the conditions in each period, so that there is an increase in each period. The average number of registrants in the first period was 21, the second period was 25.2., the third period was 107.8., the fourth period was 116.5., the fifth period was 199 and the sixth period was 344.